THE RELATIONSHIP BETWEEN THE RELIGIOSITY OF ISLAMIC TEACHINGS TO THE MENTAL HEALTH OF MODERN - Tyas Aprillia; Tri Widiyanti; Alpri Azika (Muhammadiyah International Public Health and Medicine Proceeding, 2022)
The prevalence of depression is mainly experienced by people aged over 75 years at 8.9, and the least prevalence is experienced by people aged 25-34 years at 5.4. If viewed by province, the population in Central Sulawesi Province who have cases of depression is 12.3%, and the least is in Jambi Province, as much as 1.8%. Overall in Indonesia, the population experiencing depression is 6.1% of the total population. Writing this manuscript aims to find out how the role of religion in the psychological or mental health development of modern humans through the approach of Islamic teachings. The method in a manuscript is to use a literature study or literature study by looking for existing sources, such as books and journals. Based on literature sources, it can be seen that mental health disorders are very diverse and can occur at any time and to anyone. It was also found that there was a relationship between applying Islamic teachings and mental health. Al-Quran functions as ash-Syifa or medicine to cure physical and spiritual ailments. In the Qur'an, there is a lot that explains health. Peace of mind can be achieved by remembrance (remembrance) of Allah. Prevention of poor mental health can be done through Islamic approaches.